PENGARUH PENERAPAN MODEL MODEL LEARNING CYCLE 5E PADA MATERI INVERTEBRATA TERHADAP KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR KOGNITIF SISWA KELAS X SMA MUHAMMADIYAH 7 SURABAYA - Anggi Budi Abriliyani; Yuni Gayatri; Wiwi Wikanta (Universitas Muhammadiyah Surabaya, 2017)
Abstrak: This study aims to (1). determine the effect of learning model Learning Cycle 5E on the material Invertebrates of the science process skills of students (2) the effect of the model Learning Cycle 5E on the material invertebrates effect on cognitive learning outcomes of students (3) determine the ability of teachers to manage learning biology through learning model Learning Cycle 5E in improving skills and the cognitive learning process of students. This study is a quasi experimental research with the study design using the design of